2021
DOI: 10.23937/2572-3243.1510092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors and Health Care Service Utilization for Low-Back Pain among Nigerian Automobile Technicians

Abstract: Background: Automobile technicians in resource-limited countries depend more on manual than mechanized approach in their work, and as such, may be at high risk for musculoskeletal disorders such as low back pain (LBP). This study was aimed to investigate the prevalence, risk factors and health care service utilization for LBP among Nigerian automobile technicians.Methods: A total of 240 members of the National Association of Automobile Technicians responded in this survey. A previously validated instrument on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several studies have found that the risk factors for LBP include lack of knowledge about ergonomics (Hakim and Mohsen, 2017), prolonged standing (Şimşek, Yaǧci and Şenol, 2017;Negash, Tadele and Ferede, 2022;Zewudie et al, 2022;Awosan et al, 2017), lifting heavy objects (Adesola Ojo et al, 2021;Awosan et al, 2017), and job stress (Vinstrup, Jakobsen and Andersen, 2020), and no research has been conducted on LBP in Asia using literacy studies. These studies focused only on the LBP period (Sang, Wang and Jin, 2021), LBP among healthcare students (Wong et al, 2021), and LBP in 12 random countries (Edwards et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that the risk factors for LBP include lack of knowledge about ergonomics (Hakim and Mohsen, 2017), prolonged standing (Şimşek, Yaǧci and Şenol, 2017;Negash, Tadele and Ferede, 2022;Zewudie et al, 2022;Awosan et al, 2017), lifting heavy objects (Adesola Ojo et al, 2021;Awosan et al, 2017), and job stress (Vinstrup, Jakobsen and Andersen, 2020), and no research has been conducted on LBP in Asia using literacy studies. These studies focused only on the LBP period (Sang, Wang and Jin, 2021), LBP among healthcare students (Wong et al, 2021), and LBP in 12 random countries (Edwards et al, 2017).…”
Section: Introductionmentioning
confidence: 99%